PEREMPUAN DALAM KONSTRUKSI PEMBERITAAN BENCANA - Diah Wulandari (Program Studi Ilmu Komunikasi FBIK Unissula, 2010)
Mass media is one of the agents of socialization are very influential in constructing and reconstructing gender roles. Media not only select the events and determine the source of news, but also plays a role in defining the actors and events. Through the language used, the media can say that the issue of rehabilitation and reconstruction is more important than women's issues that require cooking or sanitary equipment (for example). The media also prefer men to be a disaster news sources than women. Therefore, the media needs to have a sense of gender (gender sensitivity), but it has a sufficient understanding of the disaster. That, in the event of disaster is not just about statistics (total area affected, number of losses, the number of victims, etc.), but the media should be able to see further than that.